2014
DOI: 10.1021/jf502536e
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctional Constituent Isolated fromCitrullus colocynthisFruits and Structure–Activity Relationships of Its Analogues Show Acaricidal and Insecticidal Efficacy

Abstract: The acaricidal and insecticidal potential of the active constituent isolated from Citrullus colocynthis fruits and its structurally related analogues was evaluated by performing leaf disk, contact toxicity, and fumigant toxicity bioassays against Tetranychus urticae, Sitophilus oryzae, and Sitophilus zeamais adults. The active constituent of C. colocynthis fruits was isolated by chromatographic techniques and was identified as 4-methylquinoline on the basis of spectroscopic analyses. To investigate the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Thus, this study was aimed at exploring the anti-cancer properties of extracts from Citrullus colocynth plant of the cucurbitaceae family that has been used as a traditional medicine to control diabetes ( Zaini et al, 2011 ; Shi et al, 2014 ). Reports about the nutritional and medicinal values of this plant and presence of many bioactive molecules had initially attracted our attention ( Sawaya et al, 1983 , 1986 ; Asyaz et al, 2010 ; Marzouk et al, 2010 ; Hussain et al, 2013 , 2014 ; Jeon and Lee, 2014 ; Chawech et al, 2017 ). Moreover, Tannin-Spitz et al (2007) found that an isolate (cucurbitacin glucosides) extracted from the leaves of this plant exhibits apoptotic activity in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this study was aimed at exploring the anti-cancer properties of extracts from Citrullus colocynth plant of the cucurbitaceae family that has been used as a traditional medicine to control diabetes ( Zaini et al, 2011 ; Shi et al, 2014 ). Reports about the nutritional and medicinal values of this plant and presence of many bioactive molecules had initially attracted our attention ( Sawaya et al, 1983 , 1986 ; Asyaz et al, 2010 ; Marzouk et al, 2010 ; Hussain et al, 2013 , 2014 ; Jeon and Lee, 2014 ; Chawech et al, 2017 ). Moreover, Tannin-Spitz et al (2007) found that an isolate (cucurbitacin glucosides) extracted from the leaves of this plant exhibits apoptotic activity in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Citrullus colocynth (L.) is a valuable cucurbit plant, widely distributed in the desert areas of the world, including India, known to possess nutritional values and diverse medicinal activities, including antibacterial, antifungal, larvicidal and anti-inflammatory properties ( Sawaya et al, 1986 ; Marzouk et al, 2010 ; Chawech et al, 2017 ). Literature documents the presence of many bioactive compounds, such as cucurbitacin, phenolic acids, flavonoids, pyridine and quinolone type alkaloids and fatty acids in fruits of these herbal plants ( Hussain et al, 2013 , 2014 ; Jeon and Lee, 2014 ). This plant is traditionally used to control diabetes ( Shi et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies have reported that C. colocynthis contains different chemical families such as carbohydrates, flavonoids, alkaloids, and phenolic acids [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known concerning the other parts of the plant and only few articles report antioxidant and antibacterial activities of C. colocynthis leaf extracts [10,12,13,14]. The phytochemical content of fruits is well known for bioactive compounds such as cucurbitacins; phenolic acids and flavonoids; pyridine and quinolone-type alkaloids, fatty acids; and a volatile fraction containing small alcoholic and ketonic alkyl chains [11,15,16,17]. Among these derivatives, cucurbitacins and their glycosides have been the most studied since, to date, 20 of these highly oxygenated triterpenoids were isolated from the fruit [11,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%